USP9X integrates TGF-β and hypoxia signalings to promote ovarian cancer chemoresistance via HIF-2α-maintained stemness - Zhenlei Zhang; Xiujie Yu; Liqi Wen; Jia’nan Wang; Zhufeng Li; Yu Zhang; Jiayu Cheng; Ronglin Kan; Wanting Zhang; Yan Shen; Shukai Yuan; Li Zhao (Cell Death and Disease)
Abstract Widespread intraperitoneal metastases and chemoresistance render ovarian cancer the leading cause of gynecological malignancy-related deaths, wherein TGF-β signaling plays the pivotal role by promoting cancer stem cells (CSCs) activity. The activation mechanism and key protumorigeneic events downstream of TGF-β signaling remain incompletely understood. Here, we identify hypoxic tumor microenvironment as an initiator of TGF-β signaling to promote HIF-2α positive CSC-mediated chemoresistance in high-grade serous ovarian cancer (HGSOC). Mechanistically, deubiquitinase USP9X, as a TGF-β downstream effector, stabilizes HIF-2ɑ in a hydroxylation- and ubiquitylation-dependent manner, thus promoting stemness reprogramming. Hypoxia and TGF-β signals converge on USP9X-HIF-2ɑ axis via multi-level regulations, which in turn facilitates Smad/HIF responses. Clinically, USP9X expression correlates with TGF-β signatures, CSCs characteristics, EMT behaviors, and chemotherapy responsiveness, along with HIF-2ɑ. Antagonizing USP9X efficiently represses tumor formation, metastasis, CSCs occurrence, while increasing chemosensitivity in orthotopic tumors, patient-derived xenograft (PDX), organoid, and chemoresistant cell models, in part via restricting TGF-β and hypoxia activities. This study deciphers the critical role of hypoxic niche in stimulating TGF-β signaling, and a downstream USP9X-HIF-2ɑ proteostatic regulatory axis in priming the HGSOC stemness, thereby provides novel targeting venues to counteract TGF-β signaling in CSCs and meliorate clinical chemoresistance.